ANALISIS PENGGUNAAN BAHASA JURNALISTIK PADA MAJALAH EDISI 59 LPM DINAMIKA UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Hisan, Khairatun; Zuhriah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Given the speed at which technology develops, this does not mean that the development of print media is currently ignored by people. Many people are still interested in reading news through print media such as magazines and tabloids. Of course, not all readers pay attention to their educational background when writing news for magazines, so reporters must have some writing skills in journalistic language. The research focused on the features of the journalism language in the writing of student newspapers, journals published by the UIN SU Dynamics Student Press Institute. How do they use it according to the six characteristics of journalism language: short, concise, simple, straightforward, interesting, and clear. The research was conducted using a qualitative and descriptive method, and a data analysis phase was conducted to understand the use of journalism language in issue 59 of the same magazine dealing with the topic of sexual violence. According to EYD, the journalism languages ​​published in the magazine include features of six journalism languages, including standard language rules for the Indonesian language.